Designing a Model of Marital Violence in Women - Koohi, Morteza; Karami, Jahangir; Amiri, Hasan (Applied Family Therapy Journal (AFTJ), 2026)
Objective: The present study aimed to design and validate a comprehensive, multidimensional model of marital violence among women referring to welfare and social support services in Kermanshah.Methods and Materials: This study employed a qualitative applied design using grounded theory methodology. The research population consisted of women who had experienced marital violence and referred to social emergency services, counseling centers, and welfare-related support units in Kermanshah during 2023–2024. Data were collected through in-depth, semi-structured interviews. Purposive sampling was used, and data collection continued until theoretical saturation was achieved, resulting in 23 interviews with women victims of marital violence. In addition, 10 experts in psychology, counseling, and family studies participated in the content validation phase of the extracted model and educational protocol. Data analysis was conducted using MAXQDA 2024 Pro software following open, axial, and selective coding procedures.Findings: Data analysis led to the identification of 12 core categories organized into three higher-order dimensions: causal factors, contextual and intervening conditions, and manifestations of marital violence. The model revealed that marital violence is a multidimensional phenomenon encompassing physical, verbal, emotional, sexual, psychological, economic, and social violence, with control and domination functioning as a central organizing mechanism. Economic stressors, gender discrimination, lack of empathy, psychological problems, family history, forced marriage, addiction, and absence of support networks were identified as key drivers and sustaining factors of violence. The integration of these components formed a coherent explanatory framework suitable for intervention design.Conclusion: The findings demonstrate that marital violence is a complex, multidimensional process shaped by interacting individual, relational, and socio-cultural factors, underscoring the necessity of comprehensive, culturally responsive intervention models for prevention and support.